Epidemiological and etiological factors related to suicide in the Middle East - Aloufi, Khalid Kulaib; Alafghani, Lina Abdel; Ismail, Rawaa Ismail; Alzaid, Ban Abdullah; Alkhidhr, Mohammed Tariq; Alsubaie, Shoug Sultan; Alzaidi, Ahmed Ali; Alrubeh, Tuqa Mohammed; Abu Suliman, Talal Adnan; Alessa, Mutaz Hamad; Alzahrani, Amro Saad (International Journal Of Community Medicine And Public Health, 2021)
Estimates show that suicide is relatively common among Middle Eastern countries as a total of 26,000 fatalities in 2016 were attributable to suicide in them. However, the quality of care of mental illness in these countries is not adequate as compared to the international levels. The aim of the study was to discuss the different epidemiological and etiological factors that were linked with suicide in the Middle East, according to evidence obtained from studies in the literature. The impact of cultures and religions on dealing with mental illnesses and suicide as well as the roots of these conditions will be explored to find the appropriate solutions. Suicide in the Middle East is common but unique from other countries in the world. Religion, socio-economic status, war and conflict in many regions play a big role in the rate of suicide. Religion reduces the prevalence rates of suicide but other factors might be more dominant as many regions are in conflict and have low socio-economic status. Furthermore, gender, family conflicts and mental illnesses were identifiable risk factors in the literature. More efforts on a national level is warranted as well as among communities to reduce the rates of suicide. The initiation of support groups among those with mental illnesses and low socio-economic state will prove extremely beneficial in reducing the rate of suicide as they are almost non-existent in Middle East.